Síntese e caracterização de nanocristais de TiO2 via processo hidrotérmico e sua atividade na fotodegradação de um corante da indústria coureira - Collazzo, Gabriela Carvalho (2009)
This work reports the synthesis of TiO2 catalyst using the hydrothermal method at different synthesis conditions in order to study the influence of time and temperature on the physical properties of the material. The synthesis of titanium dioxide was based on the route of synthesis developed by Venkatachalam et al. (2007), where the calcination stage was replaced by hydrothermal treatment. The synthesis of titanium dioxide was performed at different reaction times (6, 12, 24 and 36 h) and at different temperatures (150 and 200ºC) and the molar composition of the reaction. The resultant powder was characterized by X-ray diffraction, X-ray fluorescence, scanning electron microscopy, infrared spectroscopy, spectroscopy of the UVvisible and nitrogen adsorption BET method. This work obtaining nanopowders of titanium dioxide phase anatase with high surface area and nano-sized crystallites. For studies of adsorption and photocatalytic activity of the material was chosen as the catalyst synthesized at 200°C and 12 h. The model dye for adsorption and activity was the dye Direct Black 38 . For the adsorption tests were used of the aqueous solution of azodye Direct Black 38 at different initial concentrations and studies on the kinetics, equilibrium and thermodynamic parameters of adsorption. Synthetic dye solutions with fixed volumes were prepared and added to a concentration of 1 g/L TiO2. An evaluation of the adsorption capacity on TiO2 showed the best fit of the data was obtained from the classification of Giles, through the curve of S-type. The thermodynamic parameters, it was observed that the adsorption process is endothermic, with weak forces of the Van der Walls acting, according the low value of the ∆Hº obtained (5.60 KJ/mol). With respect to positives values obtained of the ∆Gº concluded that the contribution was higher than enthalpy to the entropy contribution. The commercial titanium dioxide (P25-Degussa) was used as catalyst in a comparative test with photocatalytic material synthesized. The photocatalytic degradation of dye DB38 was studied for different initial concentrations of dye and different concentrations of catalyst, under conditions pH 2.5, temperature 25°C and fixed volume of 400 mL solution in a batch type reactor with the catalyst in suspension. The oxide produced showed efficient catalytic activity in the degradation of azodyes in aqueous solution, is similar to that of commercial TiO2 (P25- Degussa). This study of heterogeneous photocatalysis has shown that the initial concentration of dye influences the rate of degradation significantly, and that the variation of the concentration of catalyst in the range between 0.25 and 1.00 g/L has little influence on the rate of degradation.